Meningkatkan Hasil Belajar PAKat dan Gotong Royong Melalui Model PBL Fase A SD Negeri 04 Ngarak - Riki Rikardo (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Researchers found that SDN 04 Ngarak students had poor literacy and numeracy skills. Students with conditions like this tend not to be motivated to learn, therefore researchers apply one of the learning models, namely Problem-based learning. This research was conducted to (1) improve mutual cooperation through the PBL model in grade II A SDN 04 Ngarak students, (2) improve learning outcomes through the PBL model in grade II A SDN 04 Ngarak students, (3) improve learning completeness through the PBL model in grade II A SDN 04 Ngarak students. This study is a classroom action research consisting of four steps that must be carried out in each cycle. The four steps are (1) planning; (2) implementation; (3) observations; (4) reflection. The subjects of this study were 21 students. Data collection techniques in this study used tests, observation and documentation. Data analysis techniques use descriptive analysis and are explained with graphs and tables. The result of this study is that in cycle I, cognitive test results showed 29% proficient, 14% proficient, 43% viable, and 14% newly developed. The target teachers are 50% proficient, 45% proficient, 5% feasible, and 0% newly developed. In cycle II, there was a significant increase with 71% of participants in the advanced category and 29% proficient. This result exceeds the target of cycle II, which is 70% proficient and 30% proficient. Feasible and newly developed to reach 0%, in accordance with the target. With PBL, there is an improvement in learner learning outcomes, validating the effectiveness of the model in achieving learning objectives.